Evidence of the association between the Q2 mitochondrial group of Bemisia tabaci MED species (Hemiptera: Aleyrodidae) and low competitive displacement capability. - Bruno Rossitto De Marchi; Andre Bueno Gama; Hugh A Smith (PLoS ONE, 2023)
The whitefly, Bemisia tabaci (Gennadius), is one of the most serious agricultural pests worldwide. Bemisia tabaci is a cryptic species complex of more than 40 species among which the invasive MEAM1 and MED species are the most widespread and economically important. Both MEAM1 and MED present intraspecific genetic variability and some haplotypes are reported to be more invasive than others. MED can be further deconstructed into different genetic groups, including MED-Q1 and MED-Q2. However, distinct biological phenotypes discerning the different MED mitochondrial haplotypes are yet to be characterized. Competitive displacement and life-history trials were carried out between MED-Q2 and MEAM1 populations collected in Florida, USA. In addition, a phylogenetic analysis was carried out including populations from previous whitefly competitive displacement studies for identification and comparison of the MED mitochondrial groups. In contrast to other studies with MED-Q1, the MED-Q2 population from Florida is less likely to displace MEAM1 on pepper. In addition, both pepper and watermelon were a more favorable host to MEAM1 compared to MED-Q2 according to the life history trials.